A Proposal for Integrating Electronic Games at the Early Grades of Primary School in KSA - Alatwah, Saydah Mohammed (Journal of Educational and Psychological Sciences, 2022)
The aim of this study was to develop a proposal for integrating electronic games at the early grades of primary school by studying the reality of using electronic educational games. To achieve this goal، the descriptive approach was followed. The study sample consisted of (200) teachers from various disciplines and qualifications، randomly selected from the schools of north Riyadh. The study tools were used in the questionnaire as an instrument to obtain the necessary information and incorporated several axes according to the study questions and objectives. The most important results of the study are that electronic educational games are used in the primary grades to spread the culture of using technology in education and they help children to be accustomed to a technical environment by teaching them to use the new technologies. Also electronic educational games make learning outcomes memorable and motivate children to interact during the lesson. It helps in increasing speed of learning and to present the course more easily. Based on the response from members of the education community to the themes contained in the study tool، the researcher recommends that officials of the Ministry of Education to adopt the proposed vision and integrate electronic educational games among early stages students in the primary school. They should also provide incentives to teachers who combine electronic educational games in the educational process and work to enhance the ability of teachers with the basic skills necessary for the integration process.
Keywords: Proposal; Integrating Electronic Games; Early Grades of Primary School